(3TQM gOGjI GdCHgQjs - (3GdMSjfj GdnerjnHPj, bGVj ejQ, MSjf Hf eYjf GdOjf, J (B910 (3g`s ((3OhSJGfjs)
(3ChdgG (B:s
(3HSe Gddg deG QCjJ ceGd Yjf GdCYjGf hgh fhY GdEfSGf HGdGQJbGA Edi CYdGe GdaWfI hGdGgJOGA Edi CbSGe GdMceI EP HgG jUjQ GdfGXQ aj MbGFb GdCTjGA HUjQG hefg jDJi GdMceI s
(3BNQgG (B:s
(3hbjd fRdJ Edi GdCLSGe GdfHGJjI hjSei QSNG hbjd Edi GdLeGOjI cGdeYGOf hGdHSGjW hjeSi aSNG hbO jb gj JJYdb HGdCLQGe GdSeGhjI ddGSJceGd hef CQGO GdGSJbUGA aj GdMceI Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 260s
(3cTa GdXfhf (B2 / 2029s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs